Changes in the high-latitude Southern Hemisphere through the Eocene–Oligocene transition: a model–data comparison - A. T. Kennedy-Asser; D. J. Lunt; P. J. Valdes; J.-B. Ladant; J. Frieling; V. Lauretano (Climate of the Past, 2020)
The global and regional climate changed dramatically with the expansion of the Antarctic Ice Sheet at the Eocene–Oligocene transition (EOT). These large-scale changes are generally linked to declining atmospheric p CO 2 levels and/or changes in Southern Ocean gateways such as the Drake Passage around this time. To better understand the Southern Hemisphere regional climatic changes and the impact of glaciation on the Earth's oceans and atmosphere at the EOT, we compiled a database of 10 ocean and 4 land-surface temperature reconstructions from a range of proxy records and compared this with a series of fully coupled, low-resolution climate model simulations from two models (HadCM3BL and FOAM). Regional patterns in the proxy records of temperature show that cooling across the EOT was less at high latitudes and greater at mid-latitudes. While certain climate model simulations show moderate–good performance at recreating the temperature patterns shown in the data before and after the EOT, in general the model simulations do not capture the absolute latitudinal temperature gradient shown by the data, being too cold, particularly at high latitudes. When taking into account the absolute temperature before and after the EOT, as well as the change in temperature across it, simulations with a closed Drake Passage before and after the EOT or with an opening of the Drake Passage across the EOT perform poorly, whereas simulations with a drop in atmospheric p CO 2 in combination with ice growth generally perform better. This provides further support for previous research that changes in atmospheric p CO 2 are more likely to have been the driver of the EOT climatic changes, as opposed to the opening of the Drake Passage.